O fornecimento de medicamentos como garantia do direito à saúde: uma análise do resp. N.º 1.657.156/RJ como parâmetro para os julgados do TRF-5 e sua contribuição na política de incorporações do SUS - Batista, Milena de Souza (Universidade Federal Rural do Semi-Árido, 2020)
The Unified Health System (SUS) is the most significant among public health policies and is an important instrument for the promotion of fundamental rights in Brazil. One of the duties of SUS is the free supply of medicines, with the National Commission for the Incorporation of Technologies in SUS (CONITEC) an essential body to assist the Ministry of Health in the elaboration of dispensation lists, establishing the health technologies that will be made available to the public. However, in an environment where financial resources are not only scarce, but also finite, countless SUS users have turned to the Judiciary to fill the gaps not yet covered by public health policy, claiming treatments through the courts. This issue has been faced by Courts across the country, which has led the Superior Court of Justice to set objective criteriato guide the jurisdictional provisions that grant unincorporated drugs. The present study intends to investigate the adoption, by the Regional Court of the 5th Region, of the thesis established in the judgment of the appeal No. 1,657,156 / RJ. The problem is embodied in the following question: Within the scope of the decisions issued by the TRF-5, does the judicial concession of medicines not registered with RENAME contribute to the strengthening of the incorporation policy promoted by SUS through CONITEC? The research has an exploratory character and is developed through a documentary and bibliographic survey, with jurisprudential analysis. As a result, it was inferred that the favorable position of the judging body when determining the granting of a medication contributes to the strengthening of public policy.
Keywords: Medicamentos; Judicialização; Incorporação; CONITEC; Medicines; Judicialization; Incorporation; CIENCIAS SOCIAIS APLICADAS::DIREITO